Living Sensors: What Fish Physiology Tells Us About a Changing Ocean - Venkat, Chundru Sri Sai; Prashanth, B. R.; Nagendrasai, Kurapati; Sindhuja, Pothula (Chronicle of Bioresource Management, 2025)
Fish physiology has emerged as a valuable and sensitive tool for monitoring the health of marine ecosystems. As fish respond rapidly and measurably to environmental stressors such as pollution, ocean warming, acidification, and hypoxia, their physiological responses ranging from hormonal fluctuations to gill damage can serve as natural bioindicators of ocean health. This article explores how key physiological markers, including stress hormones, respiratory function, and reproductive health, provide early warnings of ecological disturbances. By integrating fish physiology into ocean monitoring programs, scientists gain a real-time, cost-effective method for detecting and understanding changes in marine environments. In the face of accelerating climate and human-driven pressures, fish are not only vital components of aquatic ecosystems but also act as sentinels alerting us to the declining state of the oceans.